1997
DOI: 10.1111/j.1600-051x.1997.tb00190.x
|View full text |Cite
|
Sign up to set email alerts
|

A short‐term clinical study design to investigate the chemical plaque inhibitory properties of mouthrinses when used as adjuncts to toothpastes: applied to chlorhexidine

Abstract: The removal of plaque by toothbrushing with toothpaste is the most common form of plaque control in the developed world. However, the use of chemical adjuncts such as mouthrinses is increasing. In practice mouthrinses and toothpaste are used together, however, in many clinical trials, employed to assess mouthrinse activity, toothpaste use is suspended. This fails to measure the effect of chemical interactions which are known to occur between toothpaste ingredients and mouthrinses. The objective of this trial w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
82
2
8

Year Published

2002
2002
2015
2015

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(98 citation statements)
references
References 16 publications
6
82
2
8
Order By: Relevance
“…5,25 However, it has not been recommended for use over long intervals because of the related side effects. 7,26 Therefore, the study of new technologies for use in association with mouth rinse is very important. The technique of PDT may offer several advantages compared to traditional antimicrobial mouth rinses.…”
Section: Discussionmentioning
confidence: 99%
“…5,25 However, it has not been recommended for use over long intervals because of the related side effects. 7,26 Therefore, the study of new technologies for use in association with mouth rinse is very important. The technique of PDT may offer several advantages compared to traditional antimicrobial mouth rinses.…”
Section: Discussionmentioning
confidence: 99%
“…All studies included subjects in good general health. Regarding periodontal health, the following definitions, criteria and diagnoses were used for inclusion: a healthy gingival condition and no pockets >5 mm or attachment loss >2 mm . None of the four studies reported the smoking status of the included participants, and consequently, this factor was not further analysed.…”
Section: Resultsmentioning
confidence: 90%
“…The studies performed by Van Strydonck used a 0.2% CHX mouthwash, whereas a 0.12% CHX mouthwash concentration was used by Owens et al . . An SLS dentifrice slurry rinse was used in Van Strydonck et al .…”
Section: Resultsmentioning
confidence: 99%
“…Um nível aceitável de higiene oral é dificilmente atingido pelo método mecânico devido à dificuldade dos pacientes, por isso agentes antimicrobianos estão sendo incorporados em soluções para bochecho e dentifrícios como suplementos a higienização tradicional (LINDHE et al, 1984;RAMBERG et al, 1992;OWENS, 1997).…”
Section: Os Principais Microrganismos Cariogênicos São Osunclassified
“…Os enxaguatórios bucais usados, antes ou após a escovação devem ser considerados como coadjuvantes na higiene oral (OWENS et al, 1997).…”
Section: Os Principais Microrganismos Cariogênicos São Osunclassified